2013
DOI: 10.1186/1865-1380-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Measuring emergency department crowding in an inner city hospital in The Netherlands

Abstract: BackgroundOvercrowding in the emergency department (ED) is an increasing problem worldwide. In The Netherlands overcrowding is not a major issue, although some urban hospitals struggle with increased throughput. In 2004, Weiss et al. created the NEDOCS tool (National Emergency Department Over Crowding Study), a web-based instrument to measure objective overcrowding with scores between 0 (not busy at all) to above 181 (disaster). In this study we tried to validate the accuracy of the NEDOCS tool by comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 9 publications
(29 reference statements)
0
26
2
5
Order By: Relevance
“…Combined with a reduction in bed capacity, this development has led to overcrowding in many emergency departments (Anneveld et al . , O'Connor et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with a reduction in bed capacity, this development has led to overcrowding in many emergency departments (Anneveld et al . , O'Connor et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, including Brazil, this problem becomes even more serious because emergency services represent the main access route to the health care system (1)(2)(3) . Previous studies have shown that overcrowding leads to increased health costs, decreased efficiency and quality of care, and increased incidence of adverse events and mortality, all of which culminate in poor performance of the health care system (4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Anneveled et al showed that NEDOCS scale could accurately predict overcrowdings in ED (16). McCarthy et al evaluated both scales' accuracy to be average and resulted that ED occupancy rate was not ideal, but its simplicity makes it feasible every time anywhere (17).…”
Section: Discussionmentioning
confidence: 99%